Problem Based Learning (PBL) with Scaffolding Approach to Improve Students' Mathematical Literacy - Fani Laffanillah Fani; Scolastika Mariani; Arief Agoestanto (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
Literacy skills are one of the skills needed by students to solve problems in real life. Therefore, it is necessary to conduct research in developing and improving students' mathematical literacy. The purpose of this research is to analyze the use of PBL with Scaffolding approach to improve students' mathematical literacy. This research method is a literature study, by taking 8 articles that discuss the application of PBL with a Scaffolding approach to improve students' mathematical literacy in Indonesia from 2018-2023. From the research results, the application of PBL with Scaffolding approach to improve students' mathematical literacy can be seen from the aspects of mathematical literacy, namely communication, mathematization, re-presenting, and reasoning and reasoning. Overall, PBL with a Scaffolding approach can improve mathematical literacy by obtaining an Effect Size value of 9.6701 in the large effect category and reinforced by the t-test calculation which found that Â then Â is rejected, which means that there is a significant difference between the average mathematical literacy of the experimental class and the control class